SOCIO-CULTURAL APPROACH TO STUDYING SOCIAL WORK - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article is devoted to review of concepts of the socio-cultural approach in the modern scientific literature, as well as to analysis of the culturological concept in the context of the mentioned approache and determining the place of socio-cultural approacheamong other existing approaches. A close link between the socio-cultural and axiological approaches are indicates. The article states that the question of value orientations of social work at all times was relevant. The value orientations of the social assistance will be determined the future of society.